Bacterial endophyte in Macropidia fuliginosa: its localisation and eradication from in vitro cultured basal-stem callus - Miyazaki, J.; Tan, Beng; Errington, Stephen; Kuo, J. (CSIRO Publishing, 2011)
Endophytic contamination reduces efficiency in micropropagation and causes plant-culture losses. Micropropagation of black kangaroo paw (Macropidia fuliginosa (Hook.) Druce) contributes both to the needs of the Western Australia’s nursery industry and towards conservation of this unique Australian wildflower, because the seeds are difficult to germinate. Plant preservative mixture (PPM), a proprietary mixture of two broad-spectrum isothiazolone biocides, has recently been used as a prophylactic anti-bacterial agent in plant-tissue culture. Its efficacy for eradicating endogenous bacterial contaminants in M. fuliginosa was demonstrated. Plantlets of M. fuliginosa were artificially infected with Sinorhizobium meliloti, a non-sporing bacterium isolated from rhizome tissues of red kangaroo paw (Anigozanthos rufus). Histological studies using light and electron microscopy revealed the presence of bacterial cells in intercellular spaces within the leaf mesophyll and in the lumen of xylem vessels after infection. Bacterial cells were also found in intercellular spaces of callus, the latter induced from the stem base of infected shoots with 0.05 mg L-1 thidiazuron. The eradication protocol involved infiltration of infected axillary buds and basal-stem calli with 5 mL L-1 PPM under vacuum. Quantitation by high-performance liquid chromatography (HPLC) revealed that callus tissue absorbed significantly more PPM than did axillary buds. Indexation of plantlets raised from PPM-treated tissues indicated successful eradication of the endophyte from basal-stem calli, and from shoots regenerated from them.